The Effect of the Aggregate Size and Ambient Temperature on the Impact Resistance of Concrete - Ekinci, Cevdet Emin; Elyigit, Belkis (Springer, 2025)
In this study, the effect of aggregate size and ambient temperature on the impact resistance of concrete was investigated experimentally. Also, it was tried to determine the behavior of normal and crushed stones in impact resistance, freeze-thaw, and compressive strength when used separately and together in concrete. No additives were used in the concrete samples. The consistency stability of fresh concrete is 80 mm. The Dmax of the aggregates is 16 mm and 31.5 mm. These specimens underwent successive impact tests at temperatures of 30 degrees C, 0 degrees C, and - 25 degrees C and were subjected to drops from heights of 25 cm and 30 cm. The resistance of the concretes to pressure and impact increased with a larger aggregate size. Notably, concrete samples containing crushed stone exhibited higher resistance to impact compared to those with normal aggregates. On moderate, the concrete samples at temperatures of 30 degrees C, 0 degrees C, and - 25 degrees C could withstand 12-14, 10-12, and 6-11 consecutive impacts, respectively. A discernible decrease in the resistance of concrete against pressure and impact was observed as the atmospheric temperature decreased.
Keywords: Impact resistance; Freezing-thawing; Compressive strength; Concrete; Crushed-stone